Green Fluorescent Proteins (GFP) Induce Apoptosis in Normal Nasopharyngeal Cells Expression - Mohd Aminudin, Mustapha; Sim, Sai Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2024)
Objective: To evaluate the effect of Green fluorescent proteins (GFP) expression on apoptosis in normal nasopharyngeal cells. Material and Methods: pTracer vector that contained GFP expression and pcDNA transfected into normal nasopharyngeal cell line. Apoptosis was accessed by measuring Caspase activities using Caspase-Glo ® 3/7 Assay kit following the manufacturer's protocol. The luminescence intensity was measured by microplate reader. Association of GFP expression with caspase activation was analysed by independent Sample T test. Results: The association between caspase activity and GFP expression are statistically significant compared to pcDNA vector control cells. Conclusion: Our results show that there is an association of GFP expression in pTracer vector with caspase activity in normal nasopharyngeal cell thus support that GFP expression induce apoptosis in normal nasopharyngeal cell.